2021
DOI: 10.3389/fmicb.2021.758465
|View full text |Cite
|
Sign up to set email alerts
|

TatD DNases Contribute to Biofilm Formation and Virulence in Trueperella pyogenes

Abstract: TatD DNases are conserved proteins in a variety of organisms and are considered potential virulence factors in Plasmodium falciparum and Streptococcus pneumoniae. However, the function of TatD DNases has not yet been determined in Trueperella pyogenes, which causes various infections in animals and leads to economic losses. In this study, we describe the roles of TatD DNases in T. pyogenes (TpTatDs). A bioinformatics analysis was performed to investigate the sequence characteristics of TpTatDs, and then the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…TatD DNases can participate in the immune-evasion process of pathogens and affect their pathogenicity [ 14 , 15 ]. We have previously found that TatD DNases could promote biofilm formation and virulence in T. pyogenes [ 16 ]. Thus, inhibiting the production and activity of TatD DNases is beneficial for reducing the biofilm formation and preventing the virulence of T. pyogenes .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…TatD DNases can participate in the immune-evasion process of pathogens and affect their pathogenicity [ 14 , 15 ]. We have previously found that TatD DNases could promote biofilm formation and virulence in T. pyogenes [ 16 ]. Thus, inhibiting the production and activity of TatD DNases is beneficial for reducing the biofilm formation and preventing the virulence of T. pyogenes .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously predicted that His106 may be involved in binding metal ions in TatD960 and probably plays a key role in the catalytic reaction. In TatD825, His164 is assumed to bind to metal ions to promote enzymatic reactions, while Asp212 is a critical amino acid residue for TatD825 to perform its function in the degradation of DNA [ 16 ]. In this study, our data suggest that luteolin can bind to His106 of TatD960 by forming a hydrogen bond.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations